The Persuasiveness of France’s Far-right Movement: The Case of Marine Le Pen - Karawita, Amali Kartika (JURNAL KOMUNIKASI INDONESIA, 2019)
Social and economic issues coupled with the growing social discontentment have led to a surge in popularity of far-right movements. In France, the far-right represented by Marine Le Pen and her party, the Front National (FN) were predicted to have a fair chance of winning the 2017 election. The rebranding of Marine Le Pen’s image and the strategy of persuasion used have helped her rise as a serious candidate and imposed the far-right in the French landscape. The present study offers an analysis of the strategy of persuasion used which includes an analysis of the discourse and the image of Marine Le Pen during the 2017 elections. The study employs qualitative method and is based on desk research, primarily speeches and social media postings. The findings of the research have shown that behind Marine Le Pen’s success lies a strategy of persuasion which first started with the policy of dédiabolisation. This policy aimed at rebranding Marine Le Pen and the FN’s image in order to create a friendly representation of the far-right and make its message acceptable. Marine Le Pen heavily relies on the use of pathos to establish her credibility and convince the public. The second part of the findings demonstrated how Marine Le Pen’s narratives and the rhetoric aimed at framing issues to create an emotional response and ultimately influence the audience in her favour. This emotional response is created through the use of sensational examples, words, generalities and scapegoating.